Peningkatan Kemampuan Menganalisis Unsur Pembangun Puisi Siswa Kelas X SMK Negeri 2 Alasa dengan Menggunakan Model Pembelajaran Generatif - Novita Sari Waruwu; Noveri Amal Jaya Harefa (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
ABSTRACT Based on the results of observations made by researchers at SMK 2 Alasa, especially in class X Accounting, the researchers obtained data that there were still many students who were unable to analyze the building blocks of poetry. The purpose of this research is to improve the ability to analyze to build poetry using the generative learning model. This class action research activity was carried out in two cycles using data collection techniques, observation sheets and assessment sheets. The subjects of this research were class X students of SMA Negeri 2 Alasa, totalling 20 students with 8 males and 12 females, in the semester even. The results showed that the average value in cycle I was 60, the highest value, the lowest value was 40. While in cycle II with an average value of 80, the highest value was 90, the lowest value was 75. The results of observing student activities in cycle I with an averagean average of 65% while in the second cycle with an average of 91%. The results of observing the performance of researchers in the first cycle with an average of 56.25% while in the second cycle is 87.5%. Based on the results of the researchers, the researchers concluded that using a generative learning model could improve the ability to analyze students’ poetry builders in class X SMK Negeri 2 Alasa in the 2022/2023 academic year. Suggestions from these results, the researcher suggests: 1) it is hoped that students will be able to increase their interest in conveying poetry. 2) for techers of SMK Negeri 2 Alasa, research can be an additional reference for learning models and material for the knowledge of field teacher’s efforts to improve the skills of SMK Negeri 2 Alasa students.